2012
DOI: 10.1002/etc.1910
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of herbicide formulations and chronic toxicity of technical‐grade trifluralin to larval green frogs (Lithobates clamitans)

Abstract: Fewer toxicity studies have been performed on herbicides than on insecticides despite heavier use of herbicides and evidence of herbicide formulation toxicity to amphibians. We conducted acute and chronic toxicity tests with the herbicide trifluralin (2,6-dinitro-N,N-dipropyl-4-(trifluoromethyl)aniline) on tadpoles. Herbicide formulations had lower median lethal concentrations than an insecticide formulation and technical-grade trifluralin. Chronic trifluralin exposure resulted in significantly smaller tadpole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Animal studies on toxic effects of insecticides are more common than of herbicides (Weir et al, 2012). In the Americas and Europe, corn cultivation has already increased in the last few decadesespecially for fodder crop production -but currently, corn cultivation is remarkably expanding for biofuel production (Landis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies on toxic effects of insecticides are more common than of herbicides (Weir et al, 2012). In the Americas and Europe, corn cultivation has already increased in the last few decadesespecially for fodder crop production -but currently, corn cultivation is remarkably expanding for biofuel production (Landis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fewer amphibian toxicological studies have been performed with herbicides, although they are applied in higher amounts than, for instance, insecticides (Weir et al 2012). Therefore, we chose an herbicide formulation as test substance that is commonly used in corn production.…”
mentioning
confidence: 98%
“…Furthermore, there are a lack of data for terrestrial amphibian exposures needed to relate our pesticide body burdens to reported LC50 or LD50 values. Estimates of lethal concentrations or doses for larval amphibians have been published for several of the pesticide active ingredients we tested (e.g., Overmyer et al 2007;Weir et al 2012), but they are much lower than the body burdens we measured in our treefrogs, which indicates significant differences in pesticide tolerance between life stages. An extensive data set on dermal pesticide LD50 values among birds has been published (Mineau et al 2001), but amphibian skin is much less keratinized and has adaptations to enhance water uptake, thus preventing a meaningful comparison.…”
Section: Exposure Versus Effectsmentioning
confidence: 94%